2021
DOI: 10.1021/acs.jpcb.1c03122
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Hydrogen-Bonded Networks in Ethanol–Water Liquid Mixtures as a Function of Temperature: Diffraction Experiments and Computer Simulations

Abstract: New X-ray and neutron diffraction experiments have been performed on ethanol–water mixtures as a function of decreasing temperature, so that such diffraction data are now available over the entire composition range. Extensive molecular dynamics simulations show that the all-atom interatomic potentials applied are adequate for gaining insight into the hydrogen-bonded network structure, as well as into its changes on cooling. Various tools have been exploited for revealing details concerning hydrogen bonding, as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Percolating of the H-bonded network was reported up to higher alcohol concentrations as the temperature decreases in 2-propanol-water [27] and ethanol-water [28] mixtures. However, on the temperature dependence of the structure of 1-propanolwater mixtures, according to our best of knowledge, only a small angle neutron scattering experiment can be found in the literature [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percolating of the H-bonded network was reported up to higher alcohol concentrations as the temperature decreases in 2-propanol-water [27] and ethanol-water [28] mixtures. However, on the temperature dependence of the structure of 1-propanolwater mixtures, according to our best of knowledge, only a small angle neutron scattering experiment can be found in the literature [9].…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the structure of alcohol-water mixtures with decreasing temperature has been examined in methanol-water, ethanol-water and 2-propanol-water mixtures [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have indicated anomalous properties of this mixture. Strong non-idealities are observed in thermodynamic, structural, 1–21 and transport properties, 10,12,13,16,22–40 like diffusion and viscosity. Most of these properties show nonmonotonic composition dependence with the extremum at ∼0.20 mole fraction of ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…Several simulation and computational studies have examined the hydrophobic hydration-induced modification in solution structure and the role of interspecies H-bonding in binary aqueous mixtures of TBA 14 23 and other alcohols. 24 29 Interestingly, studies employing TBA as an amphiphile are relatively more in number, although investigations employing other amphiphiles also focused on solute-induced distortion of water structure, solution heterogeneity, and solution dynamics. 30 32 The reason for employing TBA emerges from the fact that TBA possesses the largest aliphatic group among monohydroxy alcohols that are miscible with water at any proportion.…”
Section: Introductionmentioning
confidence: 99%